Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Consider z=f(x,y) where x = r*cos(theta) and y = r*sin(theta)

  1. Sep 8, 2013 #1
    Use the chain rule to show that

    dz/dx = (cos(theta) * dz/dr) - (1/r * sin(theta) dz/dtheta) and

    dz/dy = (sin(theta) dz/dr) + 1/r * cos(theta) dz/dtheta)

    where dz/dx, dz/dr, dz/dtheta, and dz/dy and first partial derivatives.

    Saw this a textbook the other day and I did not understand it.
  2. jcsd
  3. Sep 8, 2013 #2


    User Avatar
    Science Advisor
    Homework Helper

    The question starts with "Use the chain rule to show that dz/dx = ..."
    What does the chain rule tell you about dz/dx?
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook